A Shot at Strategy. Issue 3 (September 2015) - Moser, Richard; Newfield, Marcia; Berry, Joe; Kroik, Polina
<x xml:space="preserve">Abstract</x> Students and teachers have much in common. The possibility for solidarity and an activist alliance between students and contingent faculty is possible because of their shared position of exploitation by corporate‐style management. In order to create a strategic alliance between students and faculty certain conditions must be present: visionary proposals such as free higher education and the abolition of contingency must replace concessions and "fine‐tuning"; political equality between students and teachers must replace paternalism and patronage; aggressive rhetorical strategies that place our struggles with the frameworks of corporatization and austerity should replace status‐quo unionism. Participatory democracy and organizing must be taken seriously as the only way to revive representative structures. In order to realize our goals and principles, we need an action plan and a counter‐narrative. We can build our political capacity by knitting together existing political forces into an effective community of interest dedicated to the public good.